Penerapan BIM 3D pada Pekerjaan Struktur RSUD Dr. Iskak Tulungagung - Permana, Alung Nanda; Sutriono, Bantot; Beatrix, Michella (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Conventional Bill Of Quantity (BOQ) often faces inaccuracies in estimating structural work volumes due to limited detail and potential human error. This study aims to analyze the accuracy of quantity take off (QTO) using Building Information Modeling (BIM) through Autodesk Revit 2024 in the RSUD Dr. Iskak Tulungagung project. Research data included working drawings (shop drawings) and BOQ, which were modeled in 3D to generate structural work volumes from foundation to roof levels. The analysis revealed notable differences between the conventional method and Revit, with concrete volumes differing by 71.31 m3 or 9.46%, and reinforcement volumes differing by 267.981 kg or 4.51%. These findings confirm that Revit provides more detailed and consistent volume estimations, thereby enhancing project planning reliability while reducing manual calculation error.